Lemmatization of Reflexives in Northern Sotho - Prinsloo, D.J. (Lexikos, 1992)
The aim of this article is to evaluate current strategies in the lemmatization of reflexives in Northern Sotho. In particular the so-called "traditional" approach according to which reflexives are lemmatized randomly, as well as the more "rule orientated" alternative, will be critically evaluated mainly against the background of principles such as user friendliness, avoidance/tolerance of redundancy, constant application of rules versus ad hoc decisions, and practical versus linguistic/scientific considerations. The scope is furthermore narrowed down to learners' dictionaries with the target user defined as a mother tongue speaker of English or Afrikaans who studies Northern Sotho. Special attention is given to those cases where sound changes and or semantic shift occur in the formation of the reflexive. The importance or relevance of the category "reflexives", the scope, nature and amount of sound changes, and the viability of an in-depth frequency study on reflexives will be determined from the output of a recently conducted frequency study on 15 randomly selected Northern Sotho books and magazines. It will be concluded that due to serious shortcomings in both the traditional and rule-orientated approaches, reflexives should be lemmatized on the basis of frequency of use, which in turn will require extended studies on considerably enlarged data corpora.